Hubungan Ansietas Terhadap Respon Imun Infeksi Leukosit, Suhu Tubuh Pada Pasien Stroke di RSUD. Dr.Soedomo Trenggalek - Awan Hariyanto Awan (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Stroke is a disease that attacks suddenly and can cause disability or death. Patients who after a stroke experience phobic anxiety about the worsening of the condition experienced, after a stroke can cause an infection that affects the immune system, and anxiety affects the immune response to infection. The research design used correlational-cross-sectional non-experimental with a purposive sampling technique. The number of samples used is 30 respondents. Analysis of normality test data with Kolmogorov Smirnov paired group bivariate analysis with Spearman-rho statistical test with a significance level of ≤ 0.05. The anxiety of stroke patients varies from mild to moderate levels of anxiety. There is no significant relationship between the anxiety of stroke patients with the immune response to leukocyte infection and body temperature. correlation with body temperature is very weak (r) -0.007 (p) 0.969 > 0.05. The anxiety of stroke patients who are treated in hospitals varies and there is no significant relationship between anxiety and the immune response to leukocyte infection and body temperature in hemorrhagic and non-hemorrhagic stroke patients.